Influencia de las siembras tardías, altura y temperatura sobre la capacidad productiva de la papa - Tizio, R. (1963)
Trials were made in order to study the influence of late seedings made at different heights as well of the high temperatures upon the yielding capacity of potato varieties and seedlings. Free virus tubers of the variety Katahdin propagated since their introduction in this country in cool valleys of the province of San Luis (1.700m), were used in one of the trials. Two late seedings (november and december) were made in lowlands (Kilometro 8, 650 m) and other two in Highlands (Alta Carrera, 2.300 m) in the province of Mendoza, Argentine. A comparative test of yielding was made with the collected material. The significative difference produced by the lowland material in comparison to that of the highland was assumed as due to advances (in the physiological sense of the word) in the clones development. Such changes were due to the high mean environment and soil temperatures of the lowlands region, which gave a higher tuberization capacity. When the development is faster, it surpasses the maximun potential capacity of the clon, generating lower yieldings (first lowland seeding in relation to the second one). That pictures the phenomenon of the ecological degeneration. It is also deducted that the clon Katahdin propagated in cool or cold zonas ( valleys of San Luis, Alta Carrara) does not develop or if so it is slow. Said zones could become centers of "seed potato" production for the variety. In other tria!, the effect of high temperatures upon tubers already sprouted of varieties (White Rose, Kennebec, Huinkul) and seedlings (B-25-5)-B; P108-49. Kennebec and Huinkul decrease their yielding capacity (42 and 16 %) with high temperatures; P-108-49 increases its yield ( 4 7%). The results were taken according to the same theoretical lineament. The practical application of the described technique in order to structuriz> methods of predicting the behaviour of material for the production of seed in the region of Cuyo, is pointed out.